International price discovery in the presence of market microstructure effects - Joachim G. Grammig; Franziska J. Peter (University of Cologne, Centre for Financial Research (CFR), 2008)
This paper addresses and resolves the problems caused by microstructure effects when measuring the relative importance of home and U.S. market in the price discovery process of internationally cross listed stocks. In order to avoid large bounds for information shares, previous studies applying the Cholesky decomposition within the Hasbrouck (1995) framework had to rely on high frequency data. However, this entails a potential bias of estimated information shares induced by microstructure effects. We propose a modified approach that relies on distributional assumptions and yields unique and unbiased information shares. Our results indicate that the role of the U.S. market in the price discovery process of Canadian interlisted stocks has been severely underestimated to date. Moreover, we find that rather than stock specific factors, market design determines information shares.
Keywords: F3; G15; 330; international cross-listings; market microstructure effects; price discovery; Aktienmarkt; Börsenkurs; Marktanteil; Unvollkommene Information; Internationaler Finanzmarkt; Mikroökonomik